Concurrent newborn hearing and genetic screening of common hearing loss variants with bloodspot-based targeted next generation sequencing in Jiangxi province - Luo, Haiyan; Yang, Yan; Wang, Xinrong; Xu, Fangping; Huang, Cheng; Liu, Danping; Zhang, Liuyang; Huang, Ting; Ma, Pengpeng; Lu, Qing; Huang, Shuhui; Yang, Bicheng; et al. (Frontiers in Pediatrics, 2022)
Background and aims Concurrent hearing and genetic screening of newborns have been widely adopted as an effective strategy in early diagnosis and intervention for hearing loss in many cities in China. Here, we aimed to firstly explore the efficacy of combining conventional hearing screening with genetic screening among the large-scale newborns in Jiangxi Province. Methods A total of 24,349 newborns from Jiangxi Maternal and Child Health Hospital were enrolled in our study from April 2021 to June 2022. Newborn hearing screening was conducted using otoacoustic emission (OAE) and automated auditory brainstem response (AABR). Meanwhile, newborn dried blood spots were collected and twenty common variants in four genes, including GJB2, SLC26A4, MT-RNR1(12SrRNA), and GJB3, were screened using a BGISEQ-500 next generation sequencing platform. Whole coding regions sequencing of GJB2 and SLC26A4 were performed by Sanger sequencing and NGS, respectively. Following up of hearing for the newborns was undertaken by phone interviews. Results Among the 24,349 newborns, 7.00% (1,704/24,349) were bilaterally or unilaterally referred in their initial hearing screening, whereas 1.30% (316/24,349) exhibited bilateral or unilateral hearing loss in the repeated screening. Genetic screening revealed that 4.813% (1,172/24,349) of the screened newborns were positive for at least one mutant allele (heterozygote, homozygote, or compound heterozygote in one gene, mtDNA homoplasmy or heteroplasmy and combined variants in different genes). A total of 1,146 individuals were identified with mutant allele in one gene, including 525 of GJB2, 371 of SLC26A4, 189 as homoplasmic or heteroplasmic of MT-RNR1, and 61 of GJB3, indicating that GJB2 and SLC26A4 are the most common endemic deafness-associated genes among newborns in Jiangxi Province. Nineteen newborns were detected with combined heterozygous variants in different genes, with “c.235delC heterozygous and c.919-2A > G heterozygous” as the most prevalent genotype. Additionally, seven newborns were screened as homozygotes or compound heterozygotes responsible for congenital or late-onset prelingual hearing loss, including three cases with GJB2 c.235delC homozygous and one with SLC26A4 c.919-2A > G homozygous variant, one case with compound heterozygous variants for GJB2 and two with compound heterozygous variants for SLC26A4. Coding regions sequencing of GJB2 or SLC26A4 for overall 265 infants revealed that 14 individuals were identified as compound heterozygote with a second pathogenic variant not screened by our genetic panel. Conclusions Herein our study firstly investigated the efficacy of concurrent hearing screening and genetic screening of common hearing impairment variants among large-scale newborns in Jiangxi Province. Concurrent screening provides a more comprehensive approach for management of congenital or delayed onset prelingual hearing loss and prevention of drug-induced hearing impairment for newborns at risk as well as their maternal relatives. An insight into the molecular epidemiology for hearing loss genes among Jiangxi population will also be beneficial to the genetic counseling and birth defect prevention.